Metaphysics – symbol – landscape. On the motif of ruins in Caspar David Friedrich’s painting - Haake, Michał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The article proposes a new reading of the symbolic and metaphysical meaning of three paintings by Caspar David Friedrich with the motif of church ruins. The restoration of The Abbey in the Oakwood of 1809, carried out between 2013 and 2015, proved of particularly great help in this respect. The article is a polemic against interpretations that choose to depart from the symbolism of individual motifs. Instead, the author argues, the basis for symbolism should be sought in the structural relations that connect individual elements, i.e. the visual form of the painting. Accordingly, in consonance with the way symbols were understood after 1800, symbolism is seen as being linked to the sensory aspect of the symbolizing object. In addition, the ability of symbols to send off towards the extrasensory, the ideal, and the transcendent is rooted in the relationship between the world depicted in the paintings (a collection of motifs distributed in space) and the plane of the painting, understood, following the existential hermeneutic theory of art, as a value that is experienced in the process of perception, but is distinct from the depicted world and transcends it.

Artykuł jest propozycją nowego odczytania znaczenia symbolicznego i metafizycznego trzech obrazów Caspara Davida Friedricha z motywem ruiny kościoła. W przypadku słynnego Opactwa w dąbrowie z 1809 roku pomocna okazała się konserwacja obrazu z lat 2013–2015. Rozważania stanowią polemikę z interpretacjami, które wychodzą od symboliki poszczególnych motywów. Podstawy symboliczności obrazów niemieckiego malarza upatruje bowiem autor w relacjach strukturalnych, które te motywy łączą, czyli w wizualnej postaci dzieł. Zatem symboliczność ta – zgodnie z coraz powszechniejszym po roku 1800 rozumieniem symboli – została ujęta jako ściśle związana ze zmysłową stroną przedmiotu symbolizującego. Z kolei właściwa symbolom zdolność odsyłania ku temu, co pozazmysłowe, transcendentne i idealne, została wykazana jako zakorzeniona w relacji między światem przedstawionym na obrazach (zespołem motywów umieszczonych w pewnej przestrzeni) a płaszczyzną obrazową, rozumianą za egzystencjalno-hermeneutyczną nauką o sztuce jako wartość doświadczana w procesie percepcji obrazu, lecz nietożsama ze światem przedstawionym i transcendująca poza niego.
Metafizyka – symbol – pejzaż. Przyczynek do badań nad obrazami Caspara Davida Friedricha z motywem ruiny
Translated by Urszula Jachimczak
Keywords: Caspar David Friedrich; symbol; Romanticism; ruin; romantyzm; ruina